Intervenciones de enfermería para la prevención del cáncer de cuello uterino - Cando Tite, Gabriela Alexandra (2025)
Background: Cervical cancer prevention is based on strategies to reduce the risk of developing the disease. Nursing interventions are essential for preventing cervical cancer through education, vaccination, promoting healthy habits, encouraging Pap smears, HPV self-testing, and screening, all of which are fundamental for prevention and control. Objective: To determine the nursing interventions for cervical cancer prevention through systematic research. Methods: A qualitative approach was used, documented with studies published in indexed journals within the last 5 years. This was a descriptive study, focusing on the theme concerning similar illustrations. Inclusion criteria were established with works from Cochrane, PubMed, and Google Scholar; the search included articles in both English and Spanish. Exclusion criteria included incomplete documents, theses, monographs, studies from non-indexed pages, articles in languages other than English or Spanish, and research published before 2019. Results: The nursing professional plays a crucial role in the prevention of cervical cancer, especially in primary care, where, through proper information and continuous, appropriate education, significant progress can be made toward reducing cervical cancer. Conclusions: Nursing interventions are necessary to provide humanized care through education, healthy habits, vaccination, timely screening exams, self-education for professionals, and innovative theoretical and practical strategies and knowledge.